Perancangan Ontologi Jajanan Tradisional Khas Bali - Adnyana, I Kadek Dwi; Gunawan, I Made Suma; Mahayasa, I Gusti Agung Gede Ary; Pramartha, Cokorda (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 3 (2025): JELIKU Volume 13 No 3, February 2025DO - 10.24843/JLK.2025.v13.i03.p17, 2025)
Traditional Balinese snacks are an essential part of the cultural heritage, reflecting the culinary richness and traditions of the local community. However, preserving information related to these snacks faces several challenges, including documentation and introducing them to younger generations. This study aims to design an ontology of traditional Balinese snacks as a solution to document and preserve related information. The ontology was developed using the Methontology methodology, covering stages of specification, knowledge acquisition, conceptualization, integration, implementation, evaluation, and documentation. The resulting structured and flexible ontology was implemented using the Protégé software, encompassing classes, object properties, data properties, and individuals representing various elements of the domain of traditional Balinese snacks. Evaluation using SPARQL queries demonstrated the ontology’s effectiveness in managing information in an integrated manner. This ontology is expected to support the preservation of Balinese cultural heritage and contribute to a more dynamic knowledge management system.